A facile and novel strategy to synthesize reduced TiO2 nanotubes photoelectrode for photoelectrocatalytic degradation of diclofenac. (February 2016) - Cheng, Xiuwen; Cheng, Qingfeng; Deng, Xiaoyong; Wang, Pu; Liu, Huiling
Abstract: TiO2 nano-materials have been considered as a versatile candidate for the photoelectrochemical (PECH) applications. In this study, we reported a facile and novel strategy to synthesize reduced TiO2 nanotubes (TiO2 NTs) photoelectrode. The microwave reduction could introduce oxygen vacancy in the lattice of TiO2, while the rapid-production of oxygen vacancy facilitated the generation of impurity level between the forbidden band and greatly enhancement of visible light absorption, thereby resulting in an improved separation efficiency of photogenerated charge carriers and photocatalytic (PC) performance. Additionally, the derived valence band X-ray photoelectron spectroscopy (VBXPS) and photoluminescence (PL) spectra confirmed the existence of oxygen vacancy in the lattice of TiO2 NTs photoelectrode, in which the valence bond maximum (VBM) and charge carriers concentration of reduced TiO2 NTs photoelectrode was determined to be 1.75 eV and 5.36 × 10 19  cm −3, respectively. Furthermore, the scavenging experiments revealed that ·OH radical was the dominated species for the degradation of diclofenac. The enhanced-visible-light PC mechanism could mainly be attributed to the generation of oxygen vacancy, which can provide not only the visible light absorption capacity but also charge separation efficiency. Graphical abstract: Highlights: Reduced TiO2 NTs has been fabricated through microwave reduction treatment. Reduced TiO2 NTs photoelectrode exhibited high photoelectrocatalytic performance. Contribution of each active species to the degradation of diclofenac was studied. The enhanced visible light photocatalytic mechanism was proposed.